PERTANGGUNGJAWABAN PIDANA PENGURUS PT MITRA PAPUA VISION TERHADAP PENYIARAN TANPA IZIN PEMEGANG HAK SIAR: STUDI PUTUSAN NOMOR 510/PID.SUS/2020/PN JAP - Suryanto Hutabarat, Muhammad Topan; Marlina, Marlina; Ningsih, Suria (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Broadcasting is an important means in social, national, and state life, which functions to disseminate important information to the public. Freedom to obtain information is part of human rights regulated in Law Number 32 of 2002 concerning Broadcasting. Based on this law, there are criminal provisions that regulate the implementation of broadcasting without a permit, where violations can be subject to criminal sanctions. Article 58 letter b and Article 33 paragraph (1) regulate that broadcasting institutions are required to obtain a permit to organize broadcasts. This crime is often referred to as organizing broadcasting activities without a permit. The practice of abuse by business actors who run cable television businesses without a permit for personal gain still often occurs, this study will examine violations of economic rights to broadcasting rights committed by business actors that cause material losses to the owner of broadcasting rights which has been decided by the Jayapura District Court with decision number 510 / Pid.Sus / 2020 / PN Jap.